2022
DOI: 10.2460/javma.21.09.0410
|View full text |Cite
|
Sign up to set email alerts
|

Discharge summaries provided to owners of pets newly diagnosed with cancer exceed recommended readability levels

Abstract: OBJECTIVE To analyze the readability of discharge summaries distributed to owners of pets newly diagnosed with cancer. SAMPLE 118 discharge summaries provided to pet owners following initial consultation. PROCEDURES A database search identified records of new patients that had been presented to the North Carolina State Veterinary Hospital medical oncology service between June 2017 and January 2019. Owner-directed portions of the summaries provided at the time of discharge were copied and pasted into a docu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 24 publications
0
7
1
Order By: Relevance
“…One previous study, assessing readability within the NCSU CVM medical oncology service, reported a mean readability score of 11.9 (FKGL). 16 In that study, discharge instructions were written by attending clinicians and there were no factors assessed pertaining to individual clinician experience or understanding of readability. 16 In the present study, every discharge summary was written by a pair of third-year students from an AVMA-accredited veterinary school.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…One previous study, assessing readability within the NCSU CVM medical oncology service, reported a mean readability score of 11.9 (FKGL). 16 In that study, discharge instructions were written by attending clinicians and there were no factors assessed pertaining to individual clinician experience or understanding of readability. 16 In the present study, every discharge summary was written by a pair of third-year students from an AVMA-accredited veterinary school.…”
Section: Discussionmentioning
confidence: 99%
“…16 In that study, discharge instructions were written by attending clinicians and there were no factors assessed pertaining to individual clinician experience or understanding of readability. 16 In the present study, every discharge summary was written by a pair of third-year students from an AVMA-accredited veterinary school. The difference in FKGL readability scores between the present study and the study by Medland et al 16 could be due to discrepancies between the writing styles of students and clinicians.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations